Breaking the silence around menstruation: experiences from urban and rural India - Verma, Anjana; Patyal, Ashish; Meena, Jitendra Kumar; Mathur, Medha (International Journal Of Community Medicine And Public Health, 2021)
Menstruation being a normal physiological process is still considered a subject of shame. Discussion around “periods” is always kept private and not considered a normal health issue. There are many organizations (both government and non-government), who have been working towards providing menstrual hygiene management in India. However, even in 2020, “period” word is still associated with stigma in society. Cultural stereotypes have a huge impact in the efforts to alleviate the issues related to menstruation in India. Lack of awareness and accessibility make the behaviour change even more difficult. The ever-present stigma and taboos that adolescent girls and women face impact considerably how they understand and experience menstruation. Women are always expected to be the main source of information about menstruation. In India, especially rural areas, parents are often unprepared, uncomfortable and under-resourced to have a conversation about menstruation with their daughters. Hence it is difficult to allay the negative beliefs and attitudes that surround menstruation. The impact of shame and stigma around menstruation is an interwoven issue in Indian society felt by most of menstruating girls and women. Given the taboo around menstruation, discussions and sharing of knowledge on menstrual hygiene management practices are very limited.